2021
DOI: 10.3390/ph14050411
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Solubilization and Bioavailability of Arbidol Hydrochloride by the Preparation of Binary and Ternary β-Cyclodextrin Complexes with Poloxamer 188

Abstract: In the current study, the effect of poloxamer 188 on the complexation efficiency and dissolution of arbidol hydrochloride (ADL), a broad-spectrum antiviral agent, with β-cyclodextrin (β-CD) was investigated. Phase solubility studies confirmed a stoichiometry of a 1:1 ratio for both ADL:β-CD and ADL/β-CD with a 1% poloxamer 188 system with an AL type of phase solubility curve. The stability constants (K1:1) calculated from the AL type diagram were 550 M-1 and 2134 M-1 for AD:β-CD and ADL/β-CD with 1% poloxamer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Anwer et al formulated a ternary inclusion complex of Arbidol hydrochloride using β CD with ternary substance poloxamer 188. The dissolution result revealed 94.5% drug release in the tested 1 h [24]. Our dissolution results also showed a similar type of result using PL 188 as ternary substance.…”
Section: Dissolution Studysupporting
confidence: 82%
See 3 more Smart Citations
“…Anwer et al formulated a ternary inclusion complex of Arbidol hydrochloride using β CD with ternary substance poloxamer 188. The dissolution result revealed 94.5% drug release in the tested 1 h [24]. Our dissolution results also showed a similar type of result using PL 188 as ternary substance.…”
Section: Dissolution Studysupporting
confidence: 82%
“…Arbidol hydrochloride using poloxamer 188 and showed better stability constan 2134 M −1 [24]. The findings of our study were found to be greater than the bina and similar to the ternary systems.…”
Section: Saturation Solubility Studysupporting
confidence: 69%
See 2 more Smart Citations
“…Moreover, in another study, we demonstrated that butenafine-loaded NSs could enhance the therapeutic efficacy through channeling the drug deeper into the skin layers at the target site to completely eradicate fungal infections [ 15 ]. In addition, starch derivatives and especially, cyclodextrin-based NSs have recently emerged due to the excellent properties owing to their distinct structure [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%